Phenytoin as seizure prophylaxis in hematopoietic stem cell transplantation with busulfan conditioning - Germeraad, R. S.; Demandt, A. M. P.; Rouhl, R. P. W. (Frontiers in Neurology, 2022)
Background Phenytoin is widely used as primary seizure prophylaxis in hematopoietic stem cell transplantation in patients undergoing myeloablative conditioning with busulfan. Because of the negative side effects of phenytoin, we abandoned phenytoin use in these patients. To assess the effect of this change, we performed a retrospective cohort study on all patients receiving busulfan. Methods We included 139 patients who underwent conditioning with busulfan for hematopoietic stem cell therapy. We registered the use of phenytoin, as well as the occurrence of seizures, until 7 days after busulfan administration. We compared seizure incidence between patients who received phenytoin and those who did not. Results Of the 43 patients who received phenytoin prophylaxis, four patients (9.3%) had a seizure during the conditioning regimen, of which two patients had cerebral non-Hodgkin lymphoma. Furthermore, all these 4 patients had very high levels of phenytoin (intoxication). Of the 96 patients that did not receive phenytoin prophylaxis, three patients (3.1%) had a seizure, and one of these patients had an undefined cerebral lesion. Phenytoin did not relate to seizure prevention in a logistic regression analysis. Conclusion We conclude that phenytoin prophylaxis in patients treated with busulfan is obsolete and possibly harmful, as phenytoin intoxication can occur. We recommend discontinuing the use of phenytoin as primary seizure prophylaxis in these patients.